An Agile Data Warehouse Virtualization Framework for ROLAP Server - Menolli, André Andrade; Coelho, Ricardo Gonçalves; Silva, Glauco Carlos; Barbosa, Elielson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
In order to adapt to a competitive business scenario, the decision-making needs to be fast and reliable. In this panorama, agile business intelligence emerges as a resource to provide agile solutions. To achieve agile business intelligence solutions, organizations consider real-time data warehousing a powerful technique. Thus, we propose in this paper a framework based on data warehouse virtualization and real-time data warehousing concepts, called Agile ROLAP. The framework is comprised of an approach designed to be compatible with the main consolidated DW concepts. Furthermore, a set of components that enable the deployment of each step of the Agile ROLAP process was implemented. We evaluated our proposed approach in an experimental study where we deployed dimensional models from three distinct databases. It was analyzed the approach viability and the performance through query performance. The results indicate that the approach is viable, and the performance is satisfactory for no very large databases.